If I were you Minority and majority members evaluate relevancy and subjective experience differently while putting themselves in the other’s shoes - Dalit Milshtein; Ahmad Serhan; Simone Shamay-Tsoory (PLoS ONE, 2025)
Previous research suggests that asymmetrical power relations between minority and majority groups manifest in various cognitive biases. However, the underlying processes driving these differences remain unclear. Here we examine whether minority and majority groups exhibit differences in their basic ability to imagine outgroup-related scenarios. In two experiments, we asked participants from the majority (Israeli Jews) and minority (Israeli Arabs) groups to put themselves in their respective outgroups’ shoes. The results indicated that majority members perceived outgroup-related themes as less imaginable, relevant, and plausible to themselves compared to the minority group. These findings suggest that an individual’s social power and hierarchical position within society may influence their ability to imagine themselves and others, subsequently contributing to intergroup bias.